Antiosteoporosis medications and cardiovascular disease: a population-based nationwide nested case–control study - Tsai, Wen-Hsuan; Sung, Fung-Chang; Muo, Chih-Hsin; Tsai, Ming-Chieh; Wu, Shu-I. (Frontiers in Pharmacology, 2023)
Patients with osteoporosis are at an increased risk of cardiovascular disease (CVD). Several anti-osteoporosis medications have been demonstrated with benefit of preventing osteoporosis. Our aim is to assess the CVD risks associated with anti-osteoporosis medications using the National Health Insurance Research Database in Taiwan between 2000 2016.Methods: Among 41,102 patients of 40+ years old with newly diagnosed osteoporosis, 69.1% (N=28,387) were in the user cohort of anti-osteoporosis medicines. Of whom, 13, 472 developed CVD by the end of 2016, while 14,915 were not. Using the nested case-control analysis in the user cohort (88.0% women and 77.4% the elderly), we applied conditional logistic regression to estimate odds ratios (OR) of 8 types of CVD for the users of denosumab, bisphosphonate, teriparatide, and hormone replacement therapy (HRT).The adjusted ORs of overall CVDs were 0.13 (95% CI: 0.12 0.15) for denosumab users, 0.52 (95% CI: 0.45 0.61) for teriparatide users, and 0.80 (95% CI: 0.76 0.85) for bisphosphonate users. The HRT users were at higher odds of coronary artery and peripheral artery diseases, heart failure, pulmonary embolism, and deep vein thrombosis.Conclusions: Denosumab, teriparatide, and bisphosphonate may have more protective effects against CVD than hormone therapy. Physicians may take subsequent cardiovascular risks into account when choosing an adequate anti-osteoporosis medication for patients with osteoporosis.